ADAT ISTIADAT SAPRAHAN PERNIKAHAN PADA MASYARAKAT MELAYU DESA TUMUK MANGGIS KECAMATAN SAMBAS - NIM. A1012191208, MUAMMAR (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractIn the saprahan tradition, there are equipment used, such as saprahan cloth, saprah plates, side dish plates, drinking water cups, rice spoons, side dish spoons, large trays, small trays, and napkins. The types of saprahan can also be distinguished based on the shape and type of dish. There are daily saprahan, kaccik day saprahan, and big day saprahan. The Sambas Malay saprahan tradition has moral education values contained in it, such as mutual cooperation (ta'awun), respecting guests (ikram dhuyuf), and togetherness (ma'iyah). Saprahan also symbolizes the values of Islamic teachings, with saprahan properties and processions. So the main problem in this writing is: